Mastery of Two Foreign Languages: English and Arabic (A Study to The Students of MAN Meulaboh Aceh Barat) - Tb. Endayani (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2021)
Mastery of foreign languages ​​in this global era is very necessary to expand the network, namely education and business networks and even politics. For this reason, at the secondary school level, foreign languages ​​must be equipped, namely English and Arabic. This study aims to determine the extent of the mastery of English and Arabic students in MAN 1 Aceh Barat and how the supporting factors in learning two languages ​​at the same time. The author conducted this research using a qualitative method which will describe the ability to master the language through interviews using two English and Arabic then the interview will be assessed as a result of the test proficiency. The results showed that out of 9 students there was 1 student who could not master two languages ​​but 8 of them had the ability to speak Arabic and English. However, most of them have more difficulty mastering Arabic than English. Then, how can they learn the language well because the parents are very supportive of providing facilities in the form of language lessons or other support, besides that the environment also greatly influences language learning.